The Southern Ocean and Its Climate in CCSM4 - Weijer, Wilbert (author); Sloyan, Bernadette (author); Maltrud, Mathew (author); Jeffery, Nicole (author); Hecht, Matthew (author); Hartin, Corinne (contributor); van Sebille, Erik (author); Wainer, Ilana (author); Landrum, Laura (author) (Journal of Climate, 2012)
The new Community Climate System Model, version 4 (CCSM4), provides a powerful tool to understand and predict the earth’s climate system. Several aspects of the Southern Ocean in the CCSM4 are explored, including the surface climatology and interannual variability, simulation of key climate water masses (Antarctic Bottom Water, Subantarctic Mode Water, and Antarctic Intermediate Water), the transport and structure of the Antarctic Circumpolar Current, and interbasin exchange via the Agulhas and Tasman leakages and at the Brazil-Malvinas Confluence. It is found that the CCSM4 has varying degrees of accuracy in the simulation of the climate of the Southern Ocean when compared with observations. This study has identified aspects of the model that warrant further analysis that will result in a more comprehensive understanding of ocean--atmosphere--ice dynamics and interactions that control the earth’s climate and its variability.